Voces de paz: reflexiones de docentes de lenguas extranjeras sobre la educación para la paz - Arismendi Gómez, Fabio Alberto; Aristizábal Cardona, Astrid Johana; Cárdenas Reyes , Yeison Mauricio; Meza Taborda, Juan Pablo (Colombian Applied Linguistics Journal, 2026)
Peace education initiatives in foreign language teaching have been increasing yet remain limited. The qualitative research project reported in this article intended to create professional development spaces to reflect on this topic in Colombia through free online workshops, tailored to university foreign language educators. The workshops created collaborative spaces for teachers to deepen their understanding of concepts related to peace education. They were conducted as part of a larger project on peace discourses and education for peace carried out by a Colombian university and another French university from 2022 to 2024. In this article, we present the understandings of peace held by these three teachers, and the potential for implementation in foreign language classrooms, as well as the impact of the workshops on their professional development. Data came from recordings of the workshops, lesson plans designed by the teachers, questionnaires, and in-depth interviews. Findings reveal that teachers interpret peace education in foreign language classrooms uniquely, and the professional development workshops played a vital role in the collective construction of knowledge around this topic.